2021
DOI: 10.4103/jpbs.jpbs_333_20
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Disturbances Associated with Acute-on-chronic Liver Failure in Patients with Underlying Alcoholic Liver Diseases

Abstract: Objectives: Acute-on-chronic liver failure (ACLF), which develops in patients with underlying alcoholic liver disease (ALD), is characterized by acute deterioration of liver function and organ failures are secondary to that. The clear understanding of metabolic pathways perturbed in ALD-ACLF patients can greatly decrease the mortality and morbidity of patients through predicting outcome, guiding treatment, and monitoring response to treatment. The purpose of this study was to investigate the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These findings suggest that impaired glucose metabolism and disrupted insulin regulation in diabetes indicate disturbances in fatty acid oxidation [ 68 , 69 ]. An elevated level of circulatory PTR (for oxidative markers) and HTR (for inflammatory markers) indicates that disease-induced oxidative stress and inflammation, and hyper-activation of the immune system led to predicated disease [ 53 , 70 ]. PTR and HTR assess the body’s capacity to convert phenylalanine to tyrosine and the histidine-to-tyrosine ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that impaired glucose metabolism and disrupted insulin regulation in diabetes indicate disturbances in fatty acid oxidation [ 68 , 69 ]. An elevated level of circulatory PTR (for oxidative markers) and HTR (for inflammatory markers) indicates that disease-induced oxidative stress and inflammation, and hyper-activation of the immune system led to predicated disease [ 53 , 70 ]. PTR and HTR assess the body’s capacity to convert phenylalanine to tyrosine and the histidine-to-tyrosine ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Then, 3-hydroxy-butyrate (3HB), acetone, alanine, betaine, acetate, choline, citrate, dimethyl sulfone (DMS), creatine, dimethylamine (DMA), glutamine, glucose, glutamate, glycine, glycerol, isoleucine, isobutyrate (IsoB), leucine, lactate, phenylalanine, methanol, pyruvate, succinate, proline, serine, threonine, valine, tyrosine, histidine, and myoinositol. Following this, the metabolic profiles were utilized to estimate five key metabolic ratios, including the phenylalanine-to-tyrosine ratio (PTR), histidine-to-tyrosine ratio (HTR), and glutamate-to-glutamine ratio (EQR), as discussed in the preceding section [ 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study by Marchesini et al [ 30 ] suggested that the increase of plasma methionine in patients with cirrhosis could be attributed to the damage of liver cells and the decrease in methionine’s metabolic function. In addition, the NMR-based metabolomics analysis by Kumar et al [ 31 ] showed increased serum methionine in patients with acute-on-chronic liver failure. Moreover, our study found that plasma L-phenylalanine, L-tyrosine, and L-methionine were positively correlated with TBil and MDF, suggesting that these three amino acids may be related to the severity of diseases, and are designated as markers of disease progression in the blood.…”
Section: Discussionmentioning
confidence: 99%